Effective Strategies for Stakeholder Engagement in Business Sustainability: a Literature Study - Yano, Yano Riksan; Arifin, Anton Ludfi; Perkasa, Didin Hikmah (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Addressing global challenges such as climate change, resource depletion, and social inequality has prompted companies to adopt sustainable business practices, balancing economic goals with social and environmental responsibility. The study aims to explore strategies for effective stakeholder engagement in achieving business sustainability, by emphasizing the role of digital technology. Using qualitative descriptive methods, this study analyzes relevant literature from academic databases, critically synthesizing theory and practice to identify key strategies and challenges. The findings highlight the important role of digitalization in improving operational efficiency, transparency, and innovation. Technologies such as IoT, AI, and data analytics drive sustainable practices by improving decision-making, reducing environmental impact, and driving value creation. Examples from countries such as Singapore and Germany demonstrate the transformative potential of strategic digital integration. Along with that, stakeholder collaboration has emerged as essential to address various interests and promote accountability. Digital platforms facilitate better communication, enabling joint problem-solving and aligning business goals with the needs of society and the environment.